Association of Light’s Criteria with Pleural Fluid Procalcitonin Levels and Ultrasound Thorax with its Impact on the Management of Pleural Effusion: A Cross-sectional Study - BK Likhitha; Keertivardhan D Kulkarni; Madhav Mahawar (Journal of Clinical and Diagnostic Research)
Introduction: Pleural effusion, the abnormal accumulation of fluid in the pleural space, affects around 1.5 million people every year. Light’s criteria is routinely employed to distinguish between transudative and exudative effusions based on the test results obtained after thoracentesis. However, this procedure cannot be preferred in certain conditions due to its invasiveness. Thoracic Ultrasound (TUS) is a crucial bedside non invasive tool for identifying and differentiating pleural effusion types and helps guide treatment decisions. Light’s criteria can misdiagnose transudates as exudates, necessitating specific biomarkers like Procalcitonin (PCT). Aim: To determine ultrasound thorax findings among patients with pleural effusion and to assess the impact of these findings on management. To associate Light’s criteria with ultrasound findings and pleural fluid PCT levels. Materials and Methods: A cross-sectional study involving 89 patients diagnosed with pleural effusion was conducted at the Department of Respiratory Medicine, Shri BM Patil Medical College, Vijayapura, Karnataka, India from 2022 to 2024. Ultrasound of the thorax was performed on each patient, Light’s criteria were calculated and pleural fluid PCT levels was measured via Enzyme-linked Immunusorbent Assay (ELISA). Categorical variables between the two groups (exudative group and transudative group) were compared using the Chi-square/Mann-Whitney U test, with p<0.05 considered statistically significant. Results: The mean age of the study participants was 50.8±18.1 years. The study found that complex septate findings were the most common Ultrasonography (USG) feature, with thin septations being the most frequent, followed by anechoic findings. The majority of the cases, 49 out of 89, were unilateral, more often on the right-side. Management varied from simple effusions treated with aspiration to complex cases that required interventions like intercostal drainage tube insertion or decortication. A cut-off of 0.345 ng/mL of pleural fluid PCT level effectively distinguished transudative from exudative effusions. There was a statistically significant association (p<0.05) between ultrasound findings as well as pleural fluid PCT levels with Light’s criteria. Conclusion: In conclusion, USG findings such as complex septate and thickened pleura are highly supportive of exudative effusions in the present study, while the anechoic appearance is indicative of transudative effusions. TUS is crucial in characterising pleural effusion and guiding treatment. PCT measurement in pleural fluid further aids in distinguishing between transudative and exudative effusions and also in identifying infectious effusions from other types, optimising patient management.